Phenotypic plasticity vs. local genetic adaptation: essential oil diversity of natural immortelle (Helichrysum italicum (Roth.) G.Don) populations along eastern Adriatic coast - Ninčević Runjić, Tonka; Pljevljakušić, Dejan; Runjić, Marko; Grdiša, Martina; Šatović, Zlatko (Frontiers in Plant Science, 2025)
The essential oil of Helichrysum italicum (Roth) G.Don, commonly known as immortelle, is produced in Mediterranean countries to meet the increasing demand of the cosmetic and pharmaceutical industries. This study focused on the analysis of secondary metabolites, specifically essential oils, extracted from plants grown from the seeds of natural immortelle populations collected along the eastern Adriatic coast and cultivated ex situ under uniform conditions. Field trials were conducted to determine whether the observed variability was due to phenotypic plasticity or local genetic adaptation. Eighteen natural immortelle populations were sampled, hydrodistilled and their essential oil composition determined by gas chromatography-mass spectrometry. A total of 84 compounds were identified. Eighteen essential oil compounds were present in concentrations greater than 5% in at least one sample of 18 populations. The populations differed significantly in nine essential oil compounds: Limonene, linalool, nerol, neryl acetate, trans-caryophyllene, neryl propionate, ar-curcumene, β-selinene and δ-selinene and the differences were attributed to genetic adaptation to the native environment. Three chemotypes were identified within which the populations were grouped. Results showed a significant and strong correlation between biochemical and bioclimatic distance, with 22.4% of biochemical differentiation between populations explained by bioclimatic distance. Correlations between the 18 main compounds and the bioclimatic variables of the populations’ native environment revealed that BIO14 Precipitation of driest month and BIO15 Precipitation seasonality, were the most informative. These results can serve as a first step for future selection of immortelle populations with desirable adaptations to obtain commercial cultivars that ensure high quality immortelle essential oil.